Permeabilitas dan Perkecambahan Benih Aren (Arenga pinnata (Wurmb.) Merr.) - Nugraheni Widyawati; , Tohari; Prapto Yudono; Issirep Soemardi (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2009)
The characteristics of seed coat delay the germination of sugar palm seeds. A research was carried out to investigate the permeability of sugar palm seeds and accelerate the germination. The research consists of four experiments with purposes: 1. to investigate the distribution of water content of sugar palm seed (RCBD Factorial between part of seed : whole seed, seed coat, endosperm and embryo under three conditions: control; soaking in water and germinate, 5 replications); 2. to investigate seed permeability (RCD, 6 soaking periods, 4 replications); 3. to investigate the content of lignin and tannin in seed (RCD, 8 seed ages, 4 replications); 4. to accelerate seed germination (RCBD, 6 treatments of scarification, 4 replication).  The results showed that the permeability of sugar palm seeds to water absorption declined with seed maturity because of the increasing in lignin and tannin content. Seed germination can be accelerated with scalding on the operculum site to increase water absorption.   Key words: Sugar palm, seeds, permeability, germination